2004
DOI: 10.1159/000079747
|View full text |Cite
|
Sign up to set email alerts
|

Taste Buds: Development and Evolution

Abstract: The gustatory system in vertebrates comprises peripheral receptors (taste buds), innervated by three cranial nerves (VII, IX, and X), and a series of central neural centers and pathways. All vertebrates, with the exception of hagfishes, have taste buds. These receptors vary morphologically in different vertebrates but usually consist of at least four types of cells (dark, light, basal, and stem cells). An out-group analysis indicates that taste buds were restricted to the oropharynx, primitively, and that exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 33 publications
1
55
0
1
Order By: Relevance
“…Evans (1931) examined the brains of cyprinids, to evaluate feeding behavior and diet composition with regard to the size of gustative lobes (lobus facialis and lobus vagi). In a series of studies, Eastman & Lannoo (1995, 2001, 2003a, 2003b, 2004, 2011 found phylogenetic, ecologic and behavior correlations with format and size of brain structures in Antarctic icefishes (Nototheniiformes). Studies on brain evolution in the Teleostei have also been conducted by Ito et al (2007) on the development of main regions of the brain, and Northcutt (2004Northcutt ( , 2008 on the development of gustative lobes and of forebrain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evans (1931) examined the brains of cyprinids, to evaluate feeding behavior and diet composition with regard to the size of gustative lobes (lobus facialis and lobus vagi). In a series of studies, Eastman & Lannoo (1995, 2001, 2003a, 2003b, 2004, 2011 found phylogenetic, ecologic and behavior correlations with format and size of brain structures in Antarctic icefishes (Nototheniiformes). Studies on brain evolution in the Teleostei have also been conducted by Ito et al (2007) on the development of main regions of the brain, and Northcutt (2004Northcutt ( , 2008 on the development of gustative lobes and of forebrain.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of studies, Eastman & Lannoo (1995, 2001, 2003a, 2003b, 2004, 2011 found phylogenetic, ecologic and behavior correlations with format and size of brain structures in Antarctic icefishes (Nototheniiformes). Studies on brain evolution in the Teleostei have also been conducted by Ito et al (2007) on the development of main regions of the brain, and Northcutt (2004Northcutt ( , 2008 on the development of gustative lobes and of forebrain. More recently, some authors have focused on the association of development and behavioral responses over the brain structures (Gonda et al, 2011;Kotrschal et al, 2012;Lecchini et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Intermediate cells, in some cases, may be undifferentiated cells which derive into dark and light cells ( [5]). However, these three types of taste cells may represent different cell lineages ( [1], [2], [3], [6]).…”
Section: Taste Cellsmentioning
confidence: 99%
“…These placodes would continue to differentiate until nerve fibers reached the inner surface of the epithelium and induced the formation of taste bud primordia. Differentiation would continue until the taste cells finally gained access to the external environment through the formation of a taste pore (Northcutt 2004). This theory was taken to task when it was shown that taste buds developed in the absence of innervations in aquatic salamanders in what is known as the "early specification model" (Northcutt 2004).…”
Section: Innervationmentioning
confidence: 99%
“…Differentiation would continue until the taste cells finally gained access to the external environment through the formation of a taste pore (Northcutt 2004). This theory was taken to task when it was shown that taste buds developed in the absence of innervations in aquatic salamanders in what is known as the "early specification model" (Northcutt 2004). The gustatory epithelium is clearly predefined and expresses growth factors and morphogens long before the arrival of pioneering gustatory nerves (Hall and Bryan 1981;Nosrat, Blomlof et al 1997).…”
Section: Innervationmentioning
confidence: 99%